Nanoscale processing - Thomas, Sabu; Balakrishnan, Preetha (Micro & nano technologies., 2021)
Nanoscale Processing outlines recent advances in processing techniques for a range of nanomaterial types. New developments in the processing of nanostructured materials are being applied in diverse fields. This book offers in-depth information and analysis of a range of processing techniques for nanostructures, and also covers nanocharacterization aspects thoroughly. Topics covered include zero dimensional nanostructures, nanostructured biomaterials, carbon-based nanostructures, polymeric and liposomal nanostructures, and quantum dots. This book is an important resource for materials scientists and engineers looking to learn more about a variety of processing techniques for various nanomaterial classes, for use in both the industrial and biomedical sectors.